Cross-Cultural Pragmatic Study of Complaint Strategies in Banjarese and Javanese - Fakhira, Rifda; Sartini, Ni Wayan (LET: Linguistics, Literature and English Teaching Journal, 2024)
A cross-cultural pragmatics exploration, particularly in multicultural and multilingual settings like Indonesia, is important for understanding language used within a cultural framework. In the comparative study, Banjarese and Javanese languages are particularly underrepresented. Thus, the research investigates and compares complaint strategies that the Banjarese and Javanese use. The current study used a qualitative approach and the Discourse Completion Task (DCT), consisting of eight scenarios, to gather the data. The study consists of 50 participants, 25 Banjarese and 25 Javanese participants, ranging in age from 18 to 60 years old. The findings of the study found that Banjarese and Javanese participants utilise mostly the same strategy, namely dissatisfaction (DS) and request for repair (RR), and prefer to avoid conflict with the interlocutors. However, Banjarese participants typically prioritise immediate resolution, whereas Javanese participants prioritise expressing their dissatisfaction first. The research highlights the significant influence that cultural context has on complaint strategies and communication.